Characterization of CRISPR genetic sequences in microorganisms associated with infections in shrimp (Litopenaeus vannamei) - Parra, Ángel; Lossada, Carla; Pérez, Aleivi; Navarrete, Johnny; González, Lenin (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
In shrimp farming, the family of proteobacteria Vibrionaceae, especially the species of the genus Vibrio, represent one of the main responsible for infections in shrimp production (Litopenaeus vannamei), generating great losses to this industry. Phagotherapy emerges as a novel alternative for the control of said infections in substitution to the use of antibiotics, thanks to the specific inhibitory activity of these viruses. However, it is necessary to take into account the presence in prokaryotes of genetic sequences called clusters of regularly interspaced short palindromic repeats (CRISPR) that act as an immune system against invasion of external mobile genetic elements such as phage or plasmids. Due to its characteristics, the CRISPR/Cas system is used as a tool for gene editing. This study presents the comparative analysis of 7 CRISPR loci found in 5 sequences of complete genomes, available in the database of NCBI/GenBank, to determine the potential use of the phage strategy in shrimp farming. The CRISPR systems corresponded to types I-E, I-F and III-D. 53 % of the spacers (75/142) presented homology with plasmids, while the remaining 47 % (67/142) showed homology with bacteriophages, mostly non-typical Vibrio infective viruses. The use of phage therapy is proposed as a treatment for infections caused by members of the family Vibrionaceae in shrimp cultures, due to the low occurrence of CRISPR systems in the species studied and the low immunity to their phages, thus ensuring greater sensitivity.